Navigating Career Progression in Public Service: An Integration of Kerry B. Bernes' Synergistic Model - Ida Farida; Nani Harlinda Nurdin; Masayu Nila Juwita (Universitas Padjadjaran, 2023)
The career development of State Civil Apparatus (ASN) has an integral role in improving the quality of public services. This article wants to explore ASN career development by integrating career development models in public services. The career development model used is the Synergy Model issued by Kerry B. Bernes, which looks at existing phenomena and their suitability for answering problems that refer to the individual dimension, organizational dimension, and alignment dimension for ASN career development. To strengthen the argument for using the synergy career development model, the author uses a case study supported by a document study. The results showed that the synergy between individuals, organizations and the way they are aligned is the main key to ASN career development in public service delivery.